Urgensi Etika dan Profesionalisme Guru dalam Perspektif Islam - Bahri, Samsul; Masdin, Masdin; Marzuki, Marzuki (Institut Agama Islam Negeri Kendari, 2021)
This paper examines the urgency of ethics and professionalism in Islamic perspective. The method used in this study is descriptive-analytical approach to Islamic education. This study concludes that the relationship between teacher ethics and professionalism cannot be separated. When these two virtues are separated, the teacher slips into the teaching malpractice resulting in problems with students’ success in learning. This study also proves that Islam is very broad and firmly regulates and places importance on the ethics, profession and professionalism of the teachers.